If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 10 + 7x = -15 + -2x Reorder the terms: 10 + X + 7x = -15 + -2x Solving 10 + X + 7x = -15 + -2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + X + -10 + 7x = -15 + -10 + -2x Reorder the terms: 10 + -10 + X + 7x = -15 + -10 + -2x Combine like terms: 10 + -10 = 0 0 + X + 7x = -15 + -10 + -2x X + 7x = -15 + -10 + -2x Combine like terms: -15 + -10 = -25 X + 7x = -25 + -2x Add '-7x' to each side of the equation. X + 7x + -7x = -25 + -2x + -7x Combine like terms: 7x + -7x = 0 X + 0 = -25 + -2x + -7x X = -25 + -2x + -7x Combine like terms: -2x + -7x = -9x X = -25 + -9x Simplifying X = -25 + -9x
| x^3=168 | | 7(4s)+1=231 | | 4(2l)+6=24 | | 1.8x=6.6 | | 14x^2-84x-126=0 | | (u-7)*8=24 | | 1/9x^6-81=0 | | 12=56-2*(3*x+4) | | 2u+14=4 | | f(e-a-c)=e(f-b-(1000-c)) | | Y=12x^2-6x | | 4x+(-3+7x)= | | 15=d/-15 | | X(x-2)+2=11-2x | | 45=12-11a | | f(x)=-6/-x-6 | | 2.35-0.5= | | 4n-9=-1 | | 100-2x=38 | | ((2x-3)/(2(2x^2-3x)))=0 | | ((2x-3)/(2(x^2-3x))=0 | | X+x+(2x-5)=25 | | 26x-17y=162 | | ((3(x-4)-(3x-2))/(x-4)^2)=0 | | 6-4x=-6x+6 | | x+(x*.85)+(x*.5)=440.47 | | (5p3/q)^3 | | 9(x-4)/6 | | y=3x^2-x | | n^2-6+-16=0 | | 2(4w+8)3=-5 | | -6(2t+2)=-48 |